Housing Market Failure in a Booming Economy - McKenzie, Fiona Haslam; Rowley, Steven (Routledge, 2013)
This paper presents national data and two case studies investigating the links between housing market failure and the context of Australia’s recent resource mining boom. It demonstrates how unprecedented international demand for mineral resources resulted in critical, local housing issues in mining communities. We conclude that without careful strategic planning and understanding of the economic and social role of housing, international market dynamics can create local housing situations that are vulnerable to market and social failures. While this paper highlights the challenges inherent in managing housing issues in Australia during a mining boom, there are likely to be lessons which can be applied in international settings. These challenges include the diversity in scale, cyclical and often unpredictable nature of booms; differences in housing policy and institutional arrangements across jurisdictions and the importance of leadership in growth management and planning.